Literature Study of Problem-Based Learning Models in Reading Learning - Utami, Elva; Arono, Arono; Yunita, Wisma (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
This research aims to describe the results of the analysis some literature on learning model Problem Based Learning in Reading learning. The research method used in this study was a method or approach library research. Data collection in this study was carried out by reviewing and exploring 20 national journals that were considered relevant to the research or study. Data were analyzed by carrying out several steps, namely data reduction, data display and content analysis. The results of this literature study showed that problem-based learning methods have an impact on reading comprehension learning outcomes. The results of this analysis strengthen the findings of previous research. These results can show stronger results and conclusions that the problem-based learning approach was very suitable for teaching students to understand reading at every level of the educational unit